DISTRIBUTION OF PUMMELO Citrus maxima (Burm.) Merr. ACCESSIONS IN MAGETAN REGENCY - Yora, Rizky; Rahayu, Arifah; Nahraeni, Wini; Rochman, Nur (Universitas Djuanda Bogor, 2017)
Pummelo plants in Magetan Regency were found to spread over several villages and their accessions have their own morphological and chemical characteristics. This study was aimed at assessing the distribution and the number of pummelo accessions in Magetan Regency. The study was conducted in Magetan Regency East Java from May to July 2015. Observation was conducted on distribution marking and accession characteristics by using a survey method. Results showed that the accessions of pummelo plants grown by farmers in Tambak Mas Village were varied but they were not evenly distributed. Meanwhile, pummelo plants grown by farmers in Dukuh Village had uniform accessions with uneven distribution. Results of field observation obtained 13 pummelo accesions, namely Adas Duku, Adas Nambangan, Bali Putih, Bali Merah 1, Bali Merah 2, Gulung 1, Gulung 2, Gulung 3, Magetan, Jawa 1, Jawa 2, Jawa 3, dan Sri Nyonya. The most commonly pummelo accessions found in Tambak Mas Village were Adas Nambangan and Adas Duku. Meanwhile the most accessions planted in Bendo Village were Adas Duku and Sri Nyonya. Key words: pummelo, Adas Nambangan, Tambak Mas, Dukuh, survey method